Cinnamaldehyde‐based Natural Product as Viscosity‐Sensitive Sensor toward Liquid Safety Inspection. Issue 47 (14th December 2022) - Xu, Lingfeng; Kang, Minqing; Xiong, Fangzhi; Sui, Yan; Huang, Yanrong
Abstract: Liquids spoiled is considered gradually as a serious public problem, and heavily medical burden has been caused by this. We suspected that the viscosity level in the deterioration process is higher than those in the normal ones. For this reason, we have presented promising sustainable natural product, 4‐(dimethylamino)cinnamaldehyde (DLCA ), for monitoring micro‐environmental viscosity alterations to achieve liquid safety inspection in a high sensitivity, rapid detection, and cheap equipment dependence pathway. This natural sensor with large stokes shift of 106.8 nm and maximum emission wavelength of 486.0 nm with high signal‐to‐noise ratio intensity. DLCA is consisted of a typical dimethylamine donor and aromatic aldehyde acceptor, connected with a rotatable single and double conjugated bond. The fluorescence intensity of this natural sensor increased 70 times with the enhancement of viscosity. The interference of other microenvironments such as pH and polarity, various potential analytes can be reduced. With the assistance of the fluorescence imaging technique, DLCA could sensitively and selectively non‐invasively identify thickening efficiency of various thickeners. Furthermore, DLCA may provide an attractive way to evaluate liquid deterioration extent with viscosity as a robust marker. We expected that this unique strategy will accelerate the efficient utilization of clean and reproducible resources. Abstract : Cinnamaldehyde‐based natural product is regarded as a promising sustainable molecular tool for viscosity inspection in liquids. Based on the high sensitivity, selectivity, photostability, and wide adaptability, this natural sensor DLCA has been applied to monitor the viscosity fluctuations during the liquid deterioration process. Without any artificial preparation and chemical reagent consumption, the concept of low‐carbon development has been practised.